Secure Data Travelling User using Hybrid Cryptosystem with User Privacy Protection - Anindya Dwi Putri Islamidina; Amang Sudarsono; Titon Dutono (EMITTER International Journal of Engineering Technology, 2020)
Nowadays traveling is the activity that everyone likes the most, but sometimes there is one traveling member who is lost and confused looking for the location of the other members. When traveling, they must bring a smartphone because of its small size and easy to carry anywhere. For this reason, an Android-based smartphone application that is able to send GPS data to all travelling members is proposed. In order to secure data transmission, cryptography and group signature to ensure that only traveling members could find out the location are applied. We use hybrid cryptography, which is a combination of symmetric cryptography using AES and asymmetric cryptography using IB-mRSA. We also add group signature as verification that members are in the same traveling group. The test result showed that the proposed method is safer than the comparison method because the symmetric key is encrypted before the key is distributed, so the attacker can not know the key. The total processing time needed to send data until member get data is 2.01 s.